Improving the well-being of Canadians - Jarrett, Peter (OECD Publishing, 2021)
For many years now, a growing number of economists, policy makers, and civil society groups have pointed to the limits of using only GDP as the primary measure of national economic progress. Accordingly, a progressively greater focus has been placed on the concept of well-being and its optimal measurement, as well as its appropriate use in budgeting and other aspects of policymaking. Canada has had a long history of measuring subjective well-being and a good pre-COVID 19 record on many of its determinants but has not yet decided on an official government-wide framework. This chapter delves into the topic and then looks at some of its crucial aspects, in particular: inequality and poverty including food insecurity; housing affordability and homelessness; physical and mental health and long-term care, with a special focus on Pharmacare; and environmental conditions. It includes a special section on the problems facing Indigenous peoples and those belonging to racialise
Keywords: Economics; Canada